Sink traps as the source of transmission of OXA-48–producing Serratia marcescens in an intensive care unit. (4th October 2018) - Regev-Yochay, Gili; Smollan, Gill; Tal, Ilana; Pinas Zade, Nani; Haviv, Yael; Nudelman, Valery; Gal-Mor, Ohad; Jaber, Hanaa; Zimlichman, Eyal; Keller, Nati; Rahav, Galia
Abstract: Background: Carbapenemase-producing Enterobacteriaceae (CPE) outbreaks are mostly attributed to patient-to-patient transmission via healthcare workers. Objective: We describe successful containment of a prolonged OXA-48–producing S. marcescens outbreak after recognizing the sink traps as the source of transmission. Methods: The Sheba Medical Center intensive care unit (ICU), contains 16 single-bed, semi-closed rooms. Active CPE surveillance includes twice-weekly rectal screening of all patients. A case was defined as a patient detected with OXA-48 CPE >72 hours after admission. A root-cause analysis was used to investigate the outbreak. All samples were inoculated on chrom-agar CRE, and carbapenemase genes were detected using commercial molecular Xpert-Carba-R. Environmental and patient S. marcescens isolates were characterized using PFGE. Results: From January 2016 to May 2017, 32 OXA-48 CPE cases were detected, and 81% of these were S. marcescens. A single clone was the cause of all but the first 2 cases. The common factor in all cases was the use of relatively large amounts of tap water. The outbreak clone was detected in 2 sink outlets and 16 sink traps. In addition to routine strict infection control measures, measures taken to contain the outbreak included (1) various sink decontamination efforts, which eliminated the bacteria from the sink drains only temporarily and (2) educational intervention that engaged the ICU team and lead to high adherence to 'sink-contamination prevention guidelines.' No additional cases were detected for 12 months. Conclusions: Despite persistence of the outbreak clones in the environmental reservoir for 1 year, the outbreak was rapidly and successfully contained. Addressing sink traps as hidden reservoirs played a major role in the intervention.